Cell Polarity Protein Pals1-Associated Tight Junction Expression Is a Favorable Prognostic Marker in Clear Cell Renal Cell Carcinoma - Li, Pingping; Lan, Ping; Liu, Sheng; Wang, Yaochun; Liu, Peijun (Frontiers in Genetics, 2020)
Introduction: The Pals1-associated tight junction (PATJ) is a Crumbs (CRB) complex component that regulates epithelial cell apico-basal polarity and directional migration. This study assessed PATJ expression in clear cell renal cell carcinoma (ccRCC) vs. normal tissues and associated with ccRCC progression and prognosis. Methods: The effects of PATJ knockdown were investigated on regulation of normal kidney epithelial cell viability and protein expression in vitro. The PATJ mRNA data in ccRCC were obtained from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases and analyzed with UALCAN, LinkedOmics, Kaplan-Meier Plotter, GEPIA, and SurvExpress tools. Immunohistochemistry was performed for PATJ in tissue microarray sections (n = 150 ccRCC and 30 normal renal specimens). Normal human kidney tubular epithelial cell (HKC) cells were transfected with PATJ and negative control siRNA for cell viability CCK-8 assay, flow cytometry, and western blots. Results: The data showed that PATJ mRNA and protein were downregulated in ccRCC tissues and cell lines. Downregulation of PATJ mRNA was associated with male patients, advanced tumor stages, grades, and ccB subtypes as well as poorer overall and disease-free survival of patients. Furthermore, PATJ protein was also significantly downregulated in ccRCC tissues and associated with advanced tumor pathologic, TNM stages and poorer overall. In vitro, knockdown of PATJ expression promoted HKC proliferation and the activation of MAPK pathway proteins. Conclusions: This study revealed that a decrease of PATJ in ccRCC, which was associated with male patients, advanced tumor, and poorer survival, suggesting that PATJ may be a useful prognostic biomarker and therapeutic target for ccRCC.